Transformation of MSME Business Strategy in Facing Economic Uncertainty and Technological Change - Silvia Setia Ningrum; Umar Burhan; Mochamad Syafii (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores how Micro, Small, and Medium Enterprises (MSMEs) in Indonesia transform their business strategies in response to economic uncertainty and technological change. Utilizing a qualitative exploratory approach, data were collected through in depth interviews with MSME owners and managers across various sectors. Thematic analysis revealed three main patterns of strategic transformation: resource reallocation, innovation in products or services, and digital operational restructuring. Findings highlight that digital capability plays a moderating role, enabling MSMEs with higher digital literacy to respond proactively and maintain business continuity, while those with limited digital competence face greater difficulty adapting. The study contributes to strategic management literature by integrating external pressures and internal digital capacity into a unified framework. Practically, it underscores the importance of digital empowerment policies to support MSME resilience in volatile environments.